Pelatihan Pembuatan Virgin Coconut Oil (VCO) bagi Ibu-Ibu di Dusun Gupit Karangsewu Kulon Progo - Permadi, Adi; Firdaus, Stradivary Maulida; Suharto, Totok Eka; Munawaroh, Annisa Luthfiana; Dewi, Kartika Tunggal; Halimah, Nur; Hayuningtyas, Ratih; Rahman, Zulfan Hanif; Dimas, Doni; Pangestu, Hendry; Hapsari, Intan Tri; Pratiwi, Margaretha Herlin; Wardana, Mikael Dia; Maryudi, Maryudi (Perkumpulan Kualitama Edukatika Indonesia, 2024)
The Community service delves into the prospect of coconut processing, specifically for the production of Virgin Coconut Oil (VCO), in the Gupit area of Kulon Progo, Indonesia. VCO, celebrated for its pure and unadulterated nature, is known for its multifaceted qualities such as health benefits and significant economic value. Within this study, we have explored and defined the standards for VCO quality. In addition, we have provided comprehensive VCO production training to the local community, achieving noteworthy results that conform to the established quality criteria. The outcome of this program holds the potential not only to invigorate the local economy but also to offer an invaluable experiential learning opportunity for students and faculty alike.